Building Brand Equity of Dian Pelangi in Social Media - Rusfian, Effy (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Brand equity provides a significant contribution to long-term sales and benefits of a product. Building brand equity through social media is important due to current rapid development of marketing 3.0. This study has two (2) objectives: 1) to identify the most significant social media in building brand equity of Dian Pelangi, and 2) to identify the most prominent indicators in building brand equity of Dian Pelangi in Hijabers community. This study applies positivist paradigm. The data are collected through survey. The sampling technique used is Four Sample One Object. This is a quantitative descriptive study of four social media: Facebook, Twitter, Blog, and Website of Dian Pelangi. This study is carried out with Islamic Marketing approach. The findings of the study show that Blog is the most influential social media in building brand equity of Dian Pelangi, while the highest indicator of brand equity of Dian Pelangi is the benefits of brand image in the form of information about current trend of color.